Analysis of cultural distance’s influence on intentions to visit Spain as a tourist destination - German Gemar; Ismael P. Soler; Henar Villar (Tourism & Management Studies)
In the tourism industry, visiting tourists’ intentions have been the subject of numerous investigations for decades. However, the factors determining choices of specific tourist destinations have still not been clearly defined. The country of origin’s culture has been widely acknowledged to be a key element in variations in tourists’ behaviours. This study evaluated the capacity of cultural distance between countries of origin and Spain – as specified by Hofstede’s proposed model – to influence intentions of visiting Spain in the near future. These intentions were measured as a function of the theory of planned behaviour. The results facilitate the identification of relevant issues affecting potential tourists’ intention to visit Spain. Analyses of the data’s validity and reliability yielded satisfactory solutions that allow conclusions to be drawn about why behavioural intentions vary significantly depending on tourists’ cultural distance from Spain. The Hofstede model’s ability to explain intention to visit was, therefore, confirmed.